Prediction Score of Antegrade Chronic Total Occlusion Percutaneous Coronary Intervention Success in Dr. Kariadi Central General Hospital Semarang - Pudjiastuti, Anggit; Rifqi, Sodiqur; Sofia, Sefri Noventi (Medica Hospitalia : Journal of Clinical Medicine, 2020)
Background: Lesion characteristics of chronic total occlusion (CTO) are predictors of percutaneous coronary intervention (PCI) success. A prediction score consist of these predictors can help CTO-PCI operators. Various prediction score had been established but none had been established in Indonesian population. Methods: This observational cohort study was performed in patients underwent native vessel CTO-PCI in Dr.Kariadi Hospital during 2018. Target vessels, ostial lesion, blunt stump, calcification, long lesion, bending, side branch, bridging collateral, and retrograde collateral were angiographic variables proposed to be predictors of CTO-PCI success. All of the variables were quantitatively assessed by two observers. Bivariate and multivariate analysis used to identify independent predictors of CTO-PCI success and to establish a scoring model. Results: A total 200 patients underwent CTO-PCI procedures were included to this study. All of the procedures used antegrade approach. The prediction score established as follows: bending (1 point), calcification (2 point), blunt stump (3 point), long lesion (1 point), and poor retrograde collateral filling (2 point). Total score ranged from 0 to 9 with decreased probability of success from 92.3% to 0.5%. Score value ? 3 categorized as difficult lesion with higher risk to failure compared to score value <3 (OR 15.4; p<0.001). The score model had good calibration and discrimination in predict CTO-PCI success (AUC 0.88; p<0.001). Conclusion: Bending, calcification, blunt stump, long lesion, and poor retrograde collateral were predictors of CTO-PCI success. The score consist of these variables could predict antegrade CTO-PCI success. Keywords: chronic total occlusion; percutaneous coronary intervention; success; prediction score.